Carbon dot-sensitized urchin-like Ti3+ self-doped TiO2 photocatalysts with enhanced photoredox ability for highly efficient removal of Cr6+ and RhB. Issue 7 (15th January 2020) - Shi, Cai; Qi, Houjuan; Sun, Zhe; Qu, Keqi; Huang, Zhanhua; Li, Jian; Dong, Mengyao; Guo, Zhanhu
Abstract : Carbon dot-sensitized Ti 3+ self-doped dual-phase hierarchical titania composite photocatalysts showed enhanced photoredox ability for removing both heavy metals and organics. Abstract : In this study, carbon dot-sensitized Ti 3+ self-doped TiO2 dual-phase (TiO2− x /CDs) composite photocatalytic systems were successfully constructed using a low-temperature hydrothermal method. The TiO2− x photocatalyst showed improved photocatalytic activities for the removal of Cr 6+ and RhB under visible light. Remarkably, RhB (10 mg L −1 ) and Cr 6+ (40 mg L −1 ) solutions were degraded completely in 30 and 120 min, respectively, by the composite photocatalyst (1 g L −1 ) under visible-light irradiation. These results were much better than those of commercial P25. This fascinating photocatalytic performance was attributed to the improved photogenerated electron–hole separation efficiency from the synergistic effects of rutile and anatase, and the reduced photogenerated charge carrier recombination and facilitated visible-light absorption from the introduced CDs. This study provides a promising approach for the treatment of real wastewater using sunlight.